1989
DOI: 10.3109/02699058909004549
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and adjustment after closed-head injury: a cluster analytical approach

Abstract: This study examined the effects of coping strategies as moderators of long-term psychosocial and emotional adjustment following closed-head injury. Cluster analysis was used to separate 69 CHI patients into three clinically relevant groups on the basis of responses to the revised Ways of Coping questionnaire. The groups were then compared on a series of validation measures. There were no differences apparent between the three clusters in age, Glasgow Coma Scale score on admission to hospital, or in relatives' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…These may be grouped into three categories: problem-focused, perception-focused and emotionfocused. The use of a 'perception-focused' category is consistent with the 'reappraisal' cluster observed in Moore and Stambrook's studies [45,88,89]. For Karlovits and McColl, creating this category allows researchers to be more specific and emphasize that individuals with head injury can successfully change the meaning of potentially stressful circumstances.…”
Section: Adjustment In Individuals With Tbisupporting
confidence: 56%
See 2 more Smart Citations
“…These may be grouped into three categories: problem-focused, perception-focused and emotionfocused. The use of a 'perception-focused' category is consistent with the 'reappraisal' cluster observed in Moore and Stambrook's studies [45,88,89]. For Karlovits and McColl, creating this category allows researchers to be more specific and emphasize that individuals with head injury can successfully change the meaning of potentially stressful circumstances.…”
Section: Adjustment In Individuals With Tbisupporting
confidence: 56%
“…Other authors examined the relationships between the use of specific coping strategies and outcome variables of the adjustment process following TBI [45,[84][85][86][87][88][89]. Among them, Moore and Stambrook's team conducted several studies using a cluster analytical approach with the revised Ways of Coping Questionnaire (WOC-R [90]).…”
Section: Adjustment In Individuals With Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…dependency ; ; Moore, Stambrook, & Peters, 1989;Peters, Stambrook, Moore, & Esses, 1990, Stambrook, Moore, & Peters, 1989). A picture is emerging of significant longterm burden upon the coping resources of patients, their families, and the larger societal systems, even for some patients who sustain so-called "mild" head injury (Levin, Eisenberg, & Benton, 1989).…”
mentioning
confidence: 99%
“…However, contradictions within the research were apparent. Moore et al [23] reported no difference in adjustment between individuals who used few coping strategies and those who used more problem-focused strategies [23]. Whereas Curran et al [8] reported that 'shared coping' (e.g.…”
Section: Copingmentioning
confidence: 99%